2016
DOI: 10.1002/2015gl067451
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on an exosphere at Ceres from Hubble Space Telescope observations

Abstract: We report far ultraviolet observations of Ceres obtained with the Cosmic Origin Spectrograph (COS) of the Hubble Space Telescope in the search for atomic emissions from an exosphere. The derived brightnesses at the oxygen lines at 1304 Å and 1356 Å are consistent with zero signals within the 1σ propagated statistical uncertainties. The OI 1304 Å brightness of 0.12 ± 0.20 Rayleighs can be explained by solar resonant scattering from an atomic oxygen column density of (8.2 ± 13.4) × 1010 cm−2. Assuming that O is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…After June 21, the intensity of the gamma ray peaks was consistent with excitation by galactic cosmic rays, as observed during quiet Sun conditions ( Fig. S2) (29).…”
Section: Identification Of Energetic Electrons By Grandsupporting
confidence: 50%
See 1 more Smart Citation
“…After June 21, the intensity of the gamma ray peaks was consistent with excitation by galactic cosmic rays, as observed during quiet Sun conditions ( Fig. S2) (29).…”
Section: Identification Of Energetic Electrons By Grandsupporting
confidence: 50%
“…All of the scintillators on GRaND are read out by photomultiplier tubes. See (29) for a detailed description of the instrument.…”
Section: Identification Of Energetic Electrons By Grandmentioning
confidence: 99%
“…Two studies (A'Hearn & Feldman, ; Küppers et al, ) have reported telescopic observations of OH radicals (most likely from photodissociation of water vapor) or H 2 O molecules around Ceres, and follow‐up observations have been able to place upper limits on vapor production rates consistent within an order of magnitude of previous observations (Roth et al, ). Hydrated minerals and water ice are both possible sources of water on Ceres (e.g., Combe et al, ; Lebofsky et al, ), and A'Hearn and Feldman () suggested several possible sources of time‐variable water vapor: a polar deposit, an ice table, or a cometary impact, rich in water or OH, at the time of observation.…”
Section: Introductionmentioning
confidence: 68%
“…Ceres, the largest body in the main asteroid belt, has abundant subsurface ice at a shallow depth (Prettyman et al 2017), and therefore it must have a tenuous water exosphere. Detection of an atmosphere on Ceres has been reported, but the occurrence is only episodic (A 'Hearn & Feldman 1992;Rousselot et al 2011;Küppers et al 2014;Roth et al 2016). No instrument on the Dawn spacecraft was designed to detect an exosphere, but observations during the initial highest-altitude orbit yielded no evidence of forwardscattered light that a dust-carrying atmosphere would have produced (Russell et al 2016).…”
Section: Introductionmentioning
confidence: 99%